2014
DOI: 10.1016/j.apcata.2014.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Ion exchange resins as catalysts for the liquid-phase dehydration of 1-butanol to di-n-butyl ether

Abstract: 9This work reports the production of di-n-butyl ether (DNBE) by means of 1-butanol dehydration 10 in the liquid phase on acidic ion-exchange resins. Dehydration experiments were performed at 11 150 ºC and 40 bar on 13 styrene-codivinylbenzene ion exchangers of different morphology. By 12 comparing 1-butanol conversions to DNBE and initial reaction rates it is concluded that 13 oversulfonated resins are the most active catalysts for 1-butanol dehydration reaction whereas 14 gel-type resins that swell significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 25 publications
3
25
1
Order By: Relevance
“…Therefore, K j, L could not be experimentally determined for ethers. As expected, symmetric ethers from dehydration of C 1 –C 4 primary alcohols were not detected, since such reactions usually take place at temperatures higher than 353 K , . Fig.…”
Section: Resultssupporting
confidence: 65%
“…Therefore, K j, L could not be experimentally determined for ethers. As expected, symmetric ethers from dehydration of C 1 –C 4 primary alcohols were not detected, since such reactions usually take place at temperatures higher than 353 K , . Fig.…”
Section: Resultssupporting
confidence: 65%
“…Besides DNBE, some side products were detected in the reaction medium. Figure 1 shows the proposed reaction scheme where 1-butene can be formed by intramolecular (Pérez et al, 2014).…”
Section: Equilibrium Constantsmentioning
confidence: 99%
“…In a previous work (Pérez et al, 2014) we showed that di-n-butyl ether can be successfully synthesized through the bimolecular dehydration of 1-butanol over acidic ion-exchange resins.…”
Section: Introductionmentioning
confidence: 99%
“…No reference has been found in the open literature concerning acid resins. Notwithstanding, taking into account the activity of ion exchange resins in etherification reactions, it is expected that acidic resins could also give interesting results for this etherification …”
Section: Preparation Of Furfuralmentioning
confidence: 99%